Improving Agriculture Students’ Reading Comprehension Through Task-Based Language Teaching (TBLT) - Prasetyaningrum, Dian Islami (D3 English Program Universitas Merdeka Malang, 2018)
After knowing the problems faced by agriculture students, this study conducted to investigate the effectiveness of Task-Based Language Teaching (TBLT) in improving students’ reading comprehension. Collaborative Classroom Action Research design was used, and the participants were 22 students. The data collected using the observation checklist, field notes, and reading test. The findings showed that TBLT could be implemented to improve students’ reading comprehension in three steps: pre-task, task cycle, and post-task which included some specific activities. Suggestion addresses to the ESP lecturers who face the same challenges to apply TBLT as an effort to improve students’ reading comprehension efficiently.